INTERNATIONAL EXPERIENCE OF ADMINISTRATION OF PNEUMOCOCCAL CONJUGATED VACCINES: PROBLEMS, PROGRESS, PERSPECTIVES - M.V. Fedoseenko; L.S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2009)
This article presents the review of results of International conference on pneumococcal conjugated vaccines. Main results of international experience in the field of control of pneumococcal infection spreading are analyzed. Authors present modern data of clinical and economic effectiveness and safety of pneumococcal conjugated vaccine RCV-7, and describe experience of administration of vaccines of next generation - PCV-10 and PCV-13. Key words: children, pneumococcal infections, prophylaxis, vaccines. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):130-134)